Efficacy of Progressive Muscle Relaxation in Adults for Stress, Anxiety, and Depression: A Systematic Review - Muhammad Khir, Syazwina (Dove Medical Press, 2025)
The rise in the prevalence of mental health problems among adults worldwide has raised concerns, highlighting the critical need for evidence-based mental health interventions that are accessible, comprehensive, and effective. Previous research suggests that Progressive Muscle Relaxation (PMR) is a promising intervention widely used to reduce mental health problems. Nevertheless, the current literature on the efficacy of PMR among adults globally is fragmented, indicating a potential gap in this research area. Hence, this paper aims to systematically compile the research evidence on the efficacy of PMR in adults for stress, anxiety, and depression. The Scopus, Web of Sciences, PubMed, PsycINFO, and Cochrane Central Register of Controlled Trials were searched from the earliest available evidence to 28th March 2023. The PRISMA (Preferred Reporting Items of Systematic Reviews and Meta-analyses) guidelines were followed, and the protocol was registered on the Open Science Framework. Joanna Briggs Institute (JBI) Critical Appraisal Tools were used to assess the quality of the included studies. A total of forty-six (46) publications from sixteen (16) countries covering more than 3402 adults were included in the review. The results show that PMR are effective in reducing stress, anxiety, and depression in adults. When PMR is combined with other interventions, the combined techniques have also consistently exhibited enhanced efficacy. Moreover, findings also indicate that the efficacy of PMR is heightened when implemented in conjunction with other interventions, surpassing its standalone efficacy. This research was supported/funded by the Ministry of Higher Education (MoHE) under the Fundamental Research Grant Scheme (FRGS) (FRGS/1/2020/SS0/UTM/02/23). The review was registered on Open Science Framework (OSF) on the 7th of March 2023; DOI: https://doi.org/10.17605/OSF.IO/U2HZP.